2022
DOI: 10.3389/fonc.2022.790332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Landscape of Littoral Cell Angioma in the Spleen Based on a Comprehensive Analysis

Abstract: ObjectiveLittoral cell angioma (LCA) is currently considered to be a rare splenic tumor with malignant potential. As the epidemiology, pathogenesis, clinical manifestation, treatment, and prognosis remain unclear, the clinical diagnosis and treatment of LCA have not been standardized. Hence, we performed a comprehensive analysis of 189 observational studies comprising 435 patients to improve the current status of diagnosis and treatment.MethodsPubMed, Embase, WanFang and CNKI were searched from inception to Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 101 publications
0
13
0
1
Order By: Relevance
“…Around 150 cases have been reported worldwide. An association between LCA and autoimmune or metabolic disorders has been reported [5][6][7][8][9][10][11]. Additionally, LCA has been shown to recur after surgical excision and leads to distant metastasis [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 150 cases have been reported worldwide. An association between LCA and autoimmune or metabolic disorders has been reported [5][6][7][8][9][10][11]. Additionally, LCA has been shown to recur after surgical excision and leads to distant metastasis [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Around 150 cases have been reported worldwide with most reported cases being benign but with unspecified malignant potential [1][2][3][4][5][6]. LCA is more prevalent in Asia and South America [5][6][7][8]. It usually presents as isolated splenomegaly with a single lesion or multiple recurrent lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That then would allow diagnosing it by biopsy without mandatory having to perform a splenectomy given the benign nature of these tumors. A new study published in February 2022 suggested that an image-guided biopsy with follow-up be the optimal diagnostic choice for patients with Littoral Cell Angioma, but a pathological uncertainty is in the cytology always possible, and standard recommendations still need to be made for the diagnostic procedure [8].…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated disease is reported in rare cases and is a sign of atypical but not frankly malignant course of this entity [7]. According to a new study comprising the analysis of 435 cases of Littoral Cell Angioma, this entity should be considered as a benign vascular tumor, which is the intrasplenic manifestation of abnormal body function (due to the high rate of coexisting malignancy or immune dysfunction) [8].…”
Section: Introductionmentioning
confidence: 99%